The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12885-015-1740-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BRCA1-related molecular features and microRNAs as prognostic factors for triple negative breast cancers

Abstract: BackgroundThe BRCA1 gene plays a key role in triple negative breast cancers (TNBCs), in which its expression can be lost by multiple mechanisms: germinal mutation followed by deletion of the second allele; negative regulation by promoter methylation; or miRNA-mediated silencing. This study aimed to establish a correlation among the BRCA1-related molecular parameters, tumor characteristics and clinical follow-up of patients to find new prognostic factors.MethodsBRCA1 protein and mRNA expression was quantified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…miRNAs are small non-coding RNAs that bind to the 3' untranslated (3'UTR) region of target messenger RNAs (mRNAs); they are known to regulate gene expression and are frequently deregulated in BC. Different miRNAs, such as miR-146, 218, 335, 342, 498, 548, or 638, regulate BRCA1 mRNA expression, and could contribute to the population of IHC BRCA1-negative tumors [63,[67][68][69][70]. A critical comprehensive appraisal of these additional factors influencing BRCA1 expression is necessary, in order to better define the tumor population sensitive to CT. Additional efforts are necessary to determine the potential impact of additional events, such as loss of heterozygosity, on the population exhibiting BRCA1 promoter hypermethylation [32].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are small non-coding RNAs that bind to the 3' untranslated (3'UTR) region of target messenger RNAs (mRNAs); they are known to regulate gene expression and are frequently deregulated in BC. Different miRNAs, such as miR-146, 218, 335, 342, 498, 548, or 638, regulate BRCA1 mRNA expression, and could contribute to the population of IHC BRCA1-negative tumors [63,[67][68][69][70]. A critical comprehensive appraisal of these additional factors influencing BRCA1 expression is necessary, in order to better define the tumor population sensitive to CT. Additional efforts are necessary to determine the potential impact of additional events, such as loss of heterozygosity, on the population exhibiting BRCA1 promoter hypermethylation [32].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-548c was reported to be an independent prognostic factor for breast cancer. Patients with a good prognosis presented higher intratumoral expression of miR-548c [ 41 ]. Consistently, our meta-analysis suggested that high expression of miR-548c in EC and OC appears to correlate with better survival in patients with EC and OC, implying that miR-548c may be a new promising prognostic factor in these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…27 Previous studies have indicated that MiR-548c-5p served as a prognostic biomarker for triplenegative breast cancers. 28 MiR-548c-5p also served as a suppressor for primary liver cancer by regulating the proliferation, migration, and invasion of liver cancer cells. 29 In our study, miR-548c-5p is the most significantly downregulated DEmiRNA covering the most DEGs in COAD which supported previous studies.…”
Section: Discussionmentioning
confidence: 99%